MODELLING FACTORS INFLUENCING CONSUMERS TRUST IN E-COMMERCE IN SHANGHAI CHINA - Guan, Di; Syriac, Nellikunnel (INTI International University, 2023)
The purpose of this study is to formulate the modelon the factors which influence consumer trust in e-commerce in China in Shanghai. Previous scholars have done some researches using TAM model to analysis e-commerce, but none of them had focus on Chinese consumers. Therefore, this research focuses on Chinese consumers' trust in e-commerce. A convenience sampling questionnaire were be use as instrument for data collection. A data of 307 respondents were collected and analyzed by SPSS. Descriptive and inferential statistical analysis will be carry out to examine the relationship between the independent variables and dependent variables.